2017
DOI: 10.1272/jnms.84.215
|View full text |Cite
|
Sign up to set email alerts
|

A Real-World Retrospective Cohort Study of Combined Therapy with Bevacizumab and Paclitaxel in Japanese Patients with Metastatic Breast Cancer

Abstract: Objective: Combined therapy with bevacizumab and paclitaxel (BP regimen) as a first-line treatment has proven highly effective with good tolerance for patients with metastatic breast cancer (MBC). The objective of this study was to examine the efficacy and safety of the BP regimen for Japanese patients with MBC in real-world clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…An open-label phase II study of bevacizumab in combination with weekly paclitaxel in Japanese patients with MBC [ 19 ] suggested that the activity and tolerability of the combination therapy as first-line therapy were reproducible in the Japanese patient population; again, the incidence of peripheral neuropathy was high. Our previous cohort study [ 20 ] also verified both the high efficacy and safety of the PB regimen but disclosed a high dose reduction rate of 28% in patients who had received the initial paclitaxel dose of 90 mg/m 2 . Hence, a need to develop a chemotherapeutic regimen that is less likely to cause dose reductions in paclitaxel emerged.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…An open-label phase II study of bevacizumab in combination with weekly paclitaxel in Japanese patients with MBC [ 19 ] suggested that the activity and tolerability of the combination therapy as first-line therapy were reproducible in the Japanese patient population; again, the incidence of peripheral neuropathy was high. Our previous cohort study [ 20 ] also verified both the high efficacy and safety of the PB regimen but disclosed a high dose reduction rate of 28% in patients who had received the initial paclitaxel dose of 90 mg/m 2 . Hence, a need to develop a chemotherapeutic regimen that is less likely to cause dose reductions in paclitaxel emerged.…”
Section: Introductionmentioning
confidence: 69%
“…In our prior clinical study [ 20 ], median TTF for the PB regimen was 6.2 months (95% CI: 4.2–8.3). Therefore, we established an expected TTF of 9.0 months and a threshold TTF of 6.2 months in patients with MBC whose response to treatment is SD or better after 3 cycles (2.8 months) of the PB regimen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation